(untitled) (Journal of Coating Science and Technology, 2014)
The paper presents some new technological sequences of electron beam evaporation and deposition of high-temperature metal-ceramic coatings. The main attention is given to two-layer Me-Cr-Al-Y/ZrO2-Y2O3 coatings with transition layers of the total thickness of up to 0.2 mm. Chemical composition and structures of the main layers (metal, ceramics) and substrate/metal and metal/ceramics transition layers, as well as the respective physico-mechanical properties are considered. A method of deposition of these coatings in one technological cycle of evaporation and condensation with application of evaporation composite ingot is proposed. Examples of coating “design” and respective equipment for practical application in gas turbine construction are given.